Quantifying the reduction in sexual transmission of HIV-1 among MSM by early initiation of ART: A mathematical model - Berenguer, Juan; Parrondo, Javier; Landovitz, Raphael J. (PLOS ONE, 2020)
Background We analyzed the effect of time to initiation of antiretroviral therapy (ART) after diagnosis on the probability of HIV-1 transmission events (HIV-TE) in naïve HIV-1-infected men having sex with men (MSM). Setting Mathematical model. Methods We used discrete event simulation modeling to estimate the probability of HIV-TE in the first 8 weeks after ART initiation; we varied ART initiation from D0 to D28 after simulated “diagnosis”. The model inputs used sexual behavior parameters from the MSM population of the START trial, and transmission rates per-sex act and HIV-1 RNA from recent meta-analyses. HIV-1 RNA decay curves were modeled from the databases of Single (efavirenz [EFV] v dolutegravir [DTG]), Spring-2 (raltegravir [RAL] v DTG), and Flamingo (darunavir/ritonavir [DRVr] v DTG) trials. Results We found that the number of HIV-TE per index patient in the first 8 weeks after ART initiation increased linearly for same-day ART to initiation on day 28. Small but statistically significant advantages of integrase strand transfer inhibitors (INSTI) over EFV and DRVr were found. Conclusions Rapid, if not same-day initiation of INSTI-based ART to newly diagnosed HIV-infected MSM has the potential for substantial public health benefits related to decreases in HIV-TE.